FACTORS INFLUENCING ADOPTION OF BLOCKCHAIN TECHNOLOGY IN THE PHARMACEUTICAL SUPPLY CHAIN FOR PREVENTION OF COUNTERFEIT DRUGS: ENVIRONMENTAL PERSPECTIVE - Pillai, Mr. Mitesh; Mathur, Dr. Dhrupad; Mahdhavi, Dr. Mehregan (The journal of contemporary issues in business and government, 2022)
In regard to the pharmaceutical supply chain, the estimate of counterfeit medicines account for 10 to 15 percent. In underdeveloped nations, counterfeit pharmaceuticals account for 30 percent of total drug sales. According to the World Health Organization (WHO) [1], Counterfeiting has become one of the world’s largest and fastest growing illegal businesses and, due to increased production and distribution of counterfeit goods and their ability to be produced in large quantities in a short amount of time, annually it is projected to be worth about 600 billion USD according to the International Anti-Counterfeiting Coalition [3]. The high incidence of counterfeit medications entering the global supply chain has long been a source of concern for the pharmaceutical industry. Counterfeit medications are those that are manufactured or labelled falsely to give the impression of being real, according to the WHO [1]. Because they may contain variable quantities of the active pharmaceutical component or are made in uncontrolled and hazardous circumstances, these counterfeit medications can be harmful, if not fatal, to patients' health [4]. In addition to the negative impact on patients, counterfeit drugs have a direct impact on pharmaceutical businesses’ profits and reputations, since they cannibalise real product markets and tarnish brand image and trustworthiness [5]. To protect human health globally, the WHO, with the help of the IMPACT Group, the European Union, and the G8 combined, is determined to accomplish the aim of combating crime with the help of a digital approach such as blockchain technology. The current paper evaluates the sub factors like regulatory/government support, Industry standard, Policies & Law in terms of international regulation, Mutual trust between the stakeholder on the adoption of BCT technology in pharmaceutical supply chain for counterfeit prevention.